Globotriaosylceramide, Gb3, is an alternative functional receptor for Shiga-like toxin 2e. - Keusch, G T (1995)
We reexamined the binding specificity of the Shiga-like toxin variant associated with porcine edema disease, SLT2e, which is reported to be more cytotoxic for Vero cells than for HeLa cells, by using receptor-deficient cells and a liposomal insertion system for purified glycolipids. We found that SLT2e preferentially uses globotetraosylceramide as a receptor but can also cause cytotoxicity by using globotriaosylceramide, the SLT2 receptor. We conclude that the differential cytotoxicity of SLT2e on HeLa and Vero cells is a function of both the receptor preference of the toxin and the specific glycolipid content of the target cells being used.